Determinación de la actividad antiviral in vitro de derivados de miricetina de Marcetia taxifolia contra los virus del chikungunya, zika y dengue. (2022)
Zika, dengue and chikungunya viruses are implicated in emerging and re-emerging epidemics in tropical and subtropical countries such as Colombia, becoming a public health problem, with a negative impact on the quality of life of the population due to the morbidity and mortality associated with their sequelae. Today there is no specific antiviral treatment, only for dengue there is a vaccine whose efficacy is not clear. This makes the development of therapeutic agents essential. Plants are a key point in the search for new molecules with potential biological action since their compounds have medicinal properties. Marcetia taxifolia is a shrub of the Melastomataceae family, for which secondary metabolites have been described with in vitro antiviral activity against the human immunodeficiency virus type 1. Preclinical evaluations of potential antivirals require reliable and reproducible methods. For this reason, an RTqPCR method was standardized for the detection and quantification of viral RNA from cell cultures, with efficiencies of 100.6%, 99.63% and 100.8%, for chikungunya, zika and dengue-2, respectively. BHK-21 was selected as the cell line that allows greater viral replication of clinical isolates compared to Vero. Additionally, the antiviral activity of derivatives of the extract of Marcetia taxifolia myricetin3-rhamnoside and myricetin-3-(6-rhamnogalactoside) was evaluated in the developed in vitro model, obtaining that the two compounds presented promising EC50 < 50µg/mL against the three viruses, on the other hand the lower effectiveness of myricetin-3-(6-rhamnogalactoside) in the case of chikungunya and zika. These data provide the first evidence for the in vitro anti-chikungunya, anti-Zika and antidengue-2 activity of myricetin-3-rhamnoside and myricetin-3-(6-rhamnogalactoside).